High-ductility concrete material prepared from coral sand and preparation method

High-ductility concrete materials prepared through specific components and processes have solved the toughness and seismic resistance problems of coral sand concrete, achieving the preparation of high-toughness and low-construction-difficulty concrete, which is suitable for island construction.

CN119263754APending Publication Date: 2025-01-07UNIV OF JINAN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411479278.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Coral sand concrete has a high porosity, making it easy for harmful external substances to seep in and cause steel corrosion. Furthermore, its properties differ significantly from ordinary concrete, making it difficult to meet the seismic requirements of high-ductility concrete.

Method used

High-ductility concrete is prepared by using components such as cement, red mud, coral sand, fly ash, quartz powder, silica fume, water glass solution, basalt fiber, and glass fiber through a specific mixing and stirring process. Basalt fiber and glass fiber are used to enhance toughness, reduce cracks, and improve resistance to freeze-thaw erosion.

Benefits of technology

It improves the toughness and seismic resistance of coral sand concrete, reduces crack formation, extends service life, and reduces construction difficulty and curing time.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of constructional engineering materials, and particularly relates to a high-ductility concrete material prepared from coral sand and a preparation method of the high-ductility concrete material. Red mud; coral sand; coal ash; quartz powder; silica fume; a water glass solution; basalt fibers; glass fibers; a water reducing agent; and the balance of water. According to the method, the construction difficulty is low, the stability is good, the good aggregate pore filling effect can be achieved without the vacuum / negative pressure condition, the time needed by heating and curing is short, and operation and implementation are easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building engineering materials, and in particular relates to a high-ductility concrete material prepared by using coral sand and a preparation method thereof. Background Art

[0002] With the development of social economy, the land resources on the mainland are no longer sufficient to meet the current development needs. However, since the islands and reefs are located near the coast and far away from the inland, transportation is inconvenient and the resources on the islands are limited. If you build buildings on the islands, you must consider a series of issues such as construction costs, sources of building materials, and construction period, which brings certain difficulties to development and construction.

[0003] However, although coral sand aggregate can be used to replace ordinary aggregate to prepare concrete, and the strength of coral sand concrete can also better meet the actual engineering construction needs of islands and reefs, its porosity is large, external harmful substances are easy to penetrate into the concrete, and it contains some chloride ions and ions, which will cause durability problems such as corrosion of steel bars inside the concrete; and coral sand also has the characteristics of light weight, high angle, multiple pores (including internal pores), and irregular shape. Despite this, in order to better solve the shortage of river sand resources in the inland, the transportation cost and construction period of coastal and offshore islands and reefs, sea sand is still used in large quantities, and coral sand is also slowly used. Due to the nature of coral aggregate itself, the performance of coral concrete made from coral aggregate as a building material is not only very different from ordinary concrete, but also different from general lightweight aggregate concrete.

[0004] High-ductility concrete is a new type of cement-based composite material. Different from traditional concrete, it has the characteristic of ultra-high toughness. It is called "bendable concrete" and is often used for the reinforcement and reconstruction of buildings and cultural relics with earthquake resistance requirements. The earthquake resistance of high-ductility concrete has always been the most concerned feature in the field of scientific research and application. The promotion and application of this material has practical significance for urban renewal in my country. The earthquake resistance of high-ductility concrete is mainly affected by the toughness of the material itself. Different from general concrete, which fails when cracks appear, high-ductility concrete exposes fibers after cracks appear. Under the pulling of high-strength fibers, the high-ductility concrete matrix will still maintain a high bending and tensile strength to ensure that the building will not collapse.

[0005] Therefore, in general, it is of great significance to find a high-ductility concrete material prepared using coral sand. Summary of the invention

[0006] In order to solve the problems existing in the above-mentioned prior art, the present invention provides a high-ductility concrete material prepared using coral sand and a preparation method thereof.

[0007] The technical solution adopted by the present invention to solve its technical problem is: A high-ductility concrete material prepared by using coral sand comprises the following components: cement; red mud; coral sand; fly ash; quartz powder; silica fume; water glass solution; basalt fiber; glass fiber; water reducing agent; and residual water.

[0008] A method for preparing a high-ductility concrete material using coral sand comprises the following steps: (1) Weigh all raw materials according to the above ingredient requirements and set aside; (2) soaking the coral sand weighed in step (1) in seawater for pre-wetting for 50 minutes, then taking it out and letting it air dry for 10 minutes without dripping water for later use; (3) Mix cement, red mud, coral sand, fly ash, quartz powder and silica fume and stir them evenly for 5-15 minutes to obtain a cementitious material; (4) adding a portion of water and water glass solution; a water reducing agent to the gelling material prepared in step (3), mixing and stirring until uniform, the stirring time is 15-25 minutes, to obtain a gelled slurry; (5) adding the remaining water and basalt fiber and glass fiber to the gelled slurry prepared in step (4) and mixing and stirring until uniform. The stirring time is 15-25 minutes to obtain a high ductility concrete material. (6) pouring the obtained high ductility concrete material into a mold, placing the test mold on a vibration table in advance, and turning on the vibration table to vibrate after pouring; (7) After the vibration is completed, the module is left to stand for 24 hours for demoulding, and the module is placed in a curing box at a temperature of 25°C-28°C and a humidity of 95%-97% for curing. After the curing is completed, the final high-ductility concrete is obtained.

[0009] The present invention also has the following additional technical features: As a further specific optimization of the technical solution of the present invention, the weight parts of the components are: 220-260 parts of cement; 30-50 parts of red mud; 330-420 parts of coral sand; 100-150 parts of fly ash; 100-150 parts of quartz powder; 18-42 parts of silica fume; 34-48 parts of water glass solution; 21-84 parts of basalt fiber; 18-36 parts of glass fiber; 12-14 parts of water reducer; water is a water-cement ratio of 0.4-0.5.

[0010] As a further specific optimization of the technical solution of the present invention: the weight proportions of the components are: 220 parts of cement; 30 parts of red mud; 330 parts of coral sand; 100 parts of fly ash; 100 parts of quartz powder; 18 parts of silica fume; 34 parts of water glass solution; 21 parts of basalt fiber; 18 parts of glass fiber; 12 parts of water reducing agent; and water has a water-cement ratio of 0.4.

[0011] As a further specific optimization of the technical solution of the present invention: the weight proportions of the components are: 260 parts of cement; 50 parts of red mud; 420 parts of coral sand; 150 parts of fly ash; 150 parts of quartz powder; 42 parts of silica fume; 48 parts of water glass solution; 84 parts of basalt fiber; 36 parts of glass fiber; 14 parts of water reducer; and water is a water-cement ratio of 0.5.

[0012] As a further specific optimization of the technical solution of the present invention: the weight proportions of the components are: 230 parts of cement; 40 parts of red mud; 360 parts of coral sand; 100 parts of fly ash; 150 parts of quartz powder; 26 parts of silica fume; 40 parts of water glass solution; 40 parts of basalt fiber; 22 parts of glass fiber; 12 parts of water reducing agent; and water has a water-cement ratio of 0.44.

[0013] As a further specific optimization of the technical solution of the present invention, the weight proportions of the components are: 250 parts of cement; 45 parts of red mud; 380 parts of coral sand; 150 parts of fly ash; 150 parts of quartz powder; 38 parts of silica fume; 40 parts of water glass solution; 76 parts of basalt fiber; 32 parts of glass fiber; 11 parts of water reducer; and water is a water-cement ratio of 0.48.

[0014] As a further specific optimization of the technical solution of the present invention: the cement is high-grade P•II52.5 general-purpose Portland cement (grade 52.5 Portland cement, grade 52.5 ordinary Portland cement, grade 52.5 pozzolanic Portland cement, grade 52.5 composite Portland cement), high-grade 52.5 special Portland cement, and high-grade aluminate cement.

[0015] As a further specific optimization of the technical solution of the present invention: the red mud is red mud powder, and the red mud powder is made by air-drying red mud slurry or drying it at 90-100° C. to a moisture content of less than 3%, and then crushing it.

[0016] As a further specific optimization of the technical solution of the present invention: the particle size range of coral sand is 0.075mm-2.36mm, the main particle size is 0.5mm-1.5mm, and the fineness modulus is between 1.8-2.25.

[0017] As a further specific optimization of the technical solution of the present invention: the fly ash particle size is 5-25µm; the fly ash has a specific surface area of ​​1300m2 / kg, a loss on ignition of 2.8%, a density of 2.55g / cm3, a SiO2 content of 45.1%, a water content of 0.85%, and a fineness of 16%.

[0018] As a further specific optimization of the technical solution of the present invention: the particle size of the quartz powder is 10-60µm, and the main particle size is 20-45µm.

[0019] As a further specific optimization of the technical solution of the present invention: the particle size of silica fume is 20-80µm, and the main particle size is 30-50µm.

[0020] As a further specific optimization of the technical solution of the present invention: the molecular formula of the water glass solution is Na2O· n SiO2; the modulus n in the water glass solution sodium silicate = SiO2 / Na2O (molar ratio) is between 1.5-3.5.

[0021] As a further specific optimization of the technical solution of the present invention: the elastic modulus of basalt fiber is 91GPa-110GPa, the nominal length is 10mm, the density is 2.63g / cm3-2.65g / cm3, the single fiber diameter is 7μm-15μm, and the breaking strength is greater than 2000MPa.

[0022] As a further specific optimization of the technical solution of the present invention: the elastic modulus of the glass fiber is 70-80GPa, the nominal length is 6-12mm, the density is 2.4-2.7g / cm3, the breaking strength is 400-600Mpa, and the melting point is 680°C.

[0023] As a further specific optimization of the technical solution of the present invention: the solid content of the polycarboxylate water-reducing agent is 38%-40%, and the water reduction rate is 27%-30%. The polycarboxylate water-reducing agent can reduce the amount of water while effectively increasing the fluidity of the slurry, which is beneficial for the cementitious material to penetrate into the pores.

[0024] Compared with the prior art, the present invention has the following advantages: Advantage 1: Because basalt fiber and glass fiber can bear and disperse some of the stress generated, thereby reducing the phenomenon of stress concentration inside the concrete, the addition of basalt fiber and glass fiber can effectively prevent cracks in coral sand concrete caused by plastic shrinkage and external temperature changes during the hardening process. In addition, when cracks appear in concrete, basalt fiber and glass fiber can span the cracks and play a bridging role, forming an effective overlap and "hoop" system, so that the coral concrete changes from brittle failure to ductile failure, with high strength and toughness.

[0025] Advantage 2: The limitation of the solid content and water reduction rate of the water reducer in the present invention can effectively reduce the amount of water used in the process of mixing concrete, improve the fluidity of the concrete, and improve the strength and stability of the concrete. When the amount of water polycarboxylate water reducer is too much, it will first affect the fluidity of the concrete, resulting in excessive slump, which may cause segregation and bleeding of the concrete.

[0026] Advantage 3: The synergy of coral sand, basalt fiber and glass fiber in the present invention can also significantly improve the freeze-thaw erosion resistance of concrete under corrosive conditions and effectively extend its service life.

[0027] Advantage 4: The invention has low construction difficulty and good stability. It can achieve good aggregate pore filling effect without vacuum / negative pressure conditions. The time required for heating and curing is short and it is easy to operate. DETAILED DESCRIPTION

[0028] A high-ductility concrete material prepared using coral sand includes the following components: cement; red mud; coral sand; fly ash; quartz powder; silica fume; water glass solution; basalt fiber; glass fiber; water reducer; and the balance of water. As an optimization, the weight proportions of the components are: 220-260 parts of cement; 30-50 parts of red mud; 330-420 parts of coral sand; 100-150 parts of fly ash; 100-150 parts of quartz powder; 18-42 parts of silica fume; 34-48 parts of water glass solution; 21-84 parts of basalt fiber; 18-36 parts of glass fiber; 12-14 parts of water reducer; and water having a water-cement ratio of 0.4-0.5.

[0029] The cement is high grade P•II52.5 general purpose Portland cement (grade 52.5 Portland cement, grade 52.5 ordinary Portland cement, grade 52.5 pozzolanic Portland cement, grade 52.5 composite Portland cement), high grade 52.5 special Portland cement, and high grade aluminate cement.

[0030] The red mud is red mud powder, which is made by air-drying red mud slurry or drying it at 90-100°C until the moisture content is less than 3%, and then crushing it.

[0031] The particle size range of coral sand is 0.075mm-2.36mm, the main particle size is 0.5mm-1.5mm, and the fineness modulus is between 1.8-2.25.

[0032] The particle size of fly ash is 5-25µm; the specific surface area of ​​fly ash is 1300m2 / kg, the loss on ignition is 2.8%, the density is 2.55g / cm3, the SiO2 content is 45.1%, the water content is 0.85%, and the fineness is 16%.

[0033] The particle size of quartz powder is 10-60µm, and the main particle size is 20-45µm.

[0034] The particle size of silica fume is 20-80µm, and the main particle size is 30-50µm.

[0035] The molecular formula of water glass solution is Na2O· n SiO2; the modulus n in the water glass solution sodium silicate = SiO2 / Na2O (molar ratio) is between 1.5-3.5.

[0036] The elastic modulus of basalt fiber is 91GPa-110GPa, the nominal length is 10mm, the density is 2.63g / cm3-2.65g / cm3, the single fiber diameter is 7μm-15μm, and the breaking strength is >2000MPa.

[0037] The elastic modulus of glass fiber is 70-80GPa, the nominal length is 6-12mm, the density is 2.4-2.7g / cm3, the breaking strength is 400-600Mpa, and the melting point is 680℃.

[0038] The solid content of polycarboxylate water-reducing agent is 38%-40%, and the water reduction rate is 27%-30%. Polycarboxylate water-reducing agent can reduce the amount of water while effectively increasing the fluidity of the slurry, which is beneficial for the cementitious material to penetrate into the pores.

[0039] A method for preparing a high-ductility concrete material using coral sand comprises the following steps: (1) Weigh all raw materials according to the above ingredient requirements and set aside; (2) soaking the coral sand weighed in step (1) in seawater for pre-wetting for 50 minutes, then taking it out and letting it air dry for 10 minutes without dripping water for later use; (3) Mix cement, red mud, coral sand, fly ash, quartz powder and silica fume and stir them evenly for 5-15 minutes to obtain a cementitious material; (4) adding a portion of water and water glass solution; a water reducing agent to the gelling material prepared in step (3), mixing and stirring until uniform, the stirring time is 15-25 minutes, to obtain a gelled slurry; (5) adding the remaining water and basalt fiber and glass fiber to the gelled slurry prepared in step (4) and mixing and stirring until uniform. The stirring time is 15-25 minutes to obtain a high ductility concrete material. (6) pouring the obtained high ductility concrete material into a mold, placing the test mold on a vibration table in advance, and turning on the vibration table to vibrate after pouring; (7) After the vibration is completed, the module is left to stand for 24 hours for demoulding, and the module is placed in a curing box at a temperature of 25°C-28°C and a humidity of 95%-97% for curing. After the curing is completed, the final high-ductility concrete is obtained. Example 1

[0040] The high-ductility concrete material prepared using coral sand has the following components in weight: 220 parts of cement; 30 parts of red mud; 330 parts of coral sand; 100 parts of fly ash; 100 parts of quartz powder; 18 parts of silica fume; 34 parts of water glass solution; 21 parts of basalt fiber; 18 parts of glass fiber; 12 parts of water-reducing agent; and water has a water-cement ratio of 0.4.

[0041] The method for preparing high ductility concrete material comprises the following steps: (1) Weigh all raw materials according to the above ingredient requirements and set aside; (2) soaking the coral sand weighed in step (1) in seawater for pre-wetting for 50 minutes, then taking it out and letting it air dry for 10 minutes without dripping water for later use; (3) Mix cement, red mud, coral sand, fly ash, quartz powder and silica fume and stir them evenly for 10 minutes to obtain a cementitious material; (4) adding a portion of water and water glass solution; a water reducing agent to the gelling material prepared in step (3), mixing and stirring until uniform, the stirring time is 15 minutes, to obtain a gelling slurry; (5) adding the remaining water and basalt fiber and glass fiber to the gelled slurry prepared in step (4) and stirring the mixture until uniform. The stirring time is 15 minutes to obtain a high ductility concrete material. (6) pouring the obtained high ductility concrete material into a mold, placing the test mold on a vibration table in advance, and turning on the vibration table to vibrate after pouring; (7) After the vibration is completed, the module is left to stand for 24 hours for demoulding, and the module is placed in a curing box at a temperature of 25°C-28°C and a humidity of 95%-97% for curing. After the curing is completed, the final high-ductility concrete is obtained. Example 2

[0042] The high-ductility concrete material prepared using coral sand has the following components in weight: 260 parts of cement; 50 parts of red mud; 420 parts of coral sand; 150 parts of fly ash; 150 parts of quartz powder; 42 parts of silica fume; 48 parts of water glass solution; 84 parts of basalt fiber; 36 parts of glass fiber; 14 parts of water reducer; and water has a water-cement ratio of 0.5.

[0043] The method for preparing high ductility concrete material comprises the following steps: (1) Weigh all raw materials according to the above ingredient requirements and set aside; (2) soaking the coral sand weighed in step (1) in seawater for pre-wetting for 50 minutes, then taking it out and letting it air dry for 10 minutes without dripping water for later use; (3) Mix cement, red mud, coral sand, fly ash, quartz powder, and silica fume and stir them evenly for 8 minutes to obtain a cementitious material; (4) adding a portion of water and water glass solution; a water reducing agent to the gelling material prepared in step (3), mixing and stirring until uniform, the stirring time is 20 minutes, to obtain a gelled slurry; (5) adding the remaining water and basalt fiber and glass fiber to the gelled slurry prepared in step (4) and stirring the mixture until uniform. The stirring time is 18 minutes to obtain a high ductility concrete material. (6) pouring the obtained high ductility concrete material into a mold, placing the test mold on a vibration table in advance, and turning on the vibration table to vibrate after pouring; (7) After the vibration is completed, the module is left to stand for 24 hours for demoulding, and the module is placed in a curing box at a temperature of 25°C-28°C and a humidity of 95%-97% for curing. After the curing is completed, the final high-ductility concrete is obtained. Example 3

[0044] The high-ductility concrete material prepared using coral sand is characterized by: the weight proportions of the components are: 230 parts of cement; 40 parts of red mud; 360 parts of coral sand; 100 parts of fly ash; 150 parts of quartz powder; 26 parts of silica fume; 40 parts of water glass solution; 40 parts of basalt fiber; 22 parts of glass fiber; 12 parts of water reducing agent; and water is a water-cement ratio of 0.44.

[0045] The method for preparing high ductility concrete material comprises the following steps: (1) Weigh all raw materials according to the above ingredient requirements and set aside; (2) soaking the coral sand weighed in step (1) in seawater for pre-wetting for 50 minutes, then taking it out and letting it air dry for 10 minutes without dripping water for later use; (3) Mix cement, red mud, coral sand, fly ash, quartz powder, and silica fume and stir them evenly for 8 minutes to obtain a cementitious material; (4) adding a portion of water and water glass solution; a water reducing agent to the gelling material prepared in step (3), mixing and stirring until uniform, the stirring time is 19 minutes, to obtain a gelling slurry; (5) adding the remaining water and basalt fiber and glass fiber to the gelled slurry prepared in step (4) and stirring the mixture until uniform. The stirring time is 19 minutes to obtain a high ductility concrete material. (6) pouring the obtained high ductility concrete material into a mold, placing the test mold on a vibration table in advance, and turning on the vibration table to vibrate after pouring; (7) After the vibration is completed, the module is left to stand for 24 hours for demoulding, and the module is placed in a curing box at a temperature of 25°C-28°C and a humidity of 95%-97% for curing. After the curing is completed, the final high-ductility concrete is obtained. Example 4

[0046] The high-ductility concrete material prepared using coral sand has the following components in weight: 250 parts of cement; 45 parts of red mud; 380 parts of coral sand; 150 parts of fly ash; 150 parts of quartz powder; 38 parts of silica fume; 40 parts of water glass solution; 76 parts of basalt fiber; 32 parts of glass fiber; 11 parts of water reducer; and water has a water-cement ratio of 0.48.

[0047] The method for preparing high ductility concrete material comprises the following steps: (1) Weigh all raw materials according to the above ingredient requirements and set aside; (2) soaking the coral sand weighed in step (1) in seawater for pre-wetting for 50 minutes, then taking it out and letting it air dry for 10 minutes without dripping water for later use; (3) Mix cement, red mud, coral sand, fly ash, quartz powder and silica fume and stir them evenly for 5-15 minutes to obtain a cementitious material; (4) adding a portion of water and water glass solution; a water reducing agent to the gelling material prepared in step (3), mixing and stirring until uniform, the stirring time is 17 minutes, to obtain a gelling slurry; (5) adding the remaining water and basalt fiber and glass fiber to the gelled slurry prepared in step (4) and mixing and stirring until uniform. The stirring time is 20 minutes to obtain a high ductility concrete material. (6) pouring the obtained high ductility concrete material into a mold, placing the test mold on a vibration table in advance, and turning on the vibration table to vibrate after pouring; (7) After the vibration is completed, the module is left to stand for 24 hours for demoulding, and the module is placed in a curing box at a temperature of 25°C-28°C and a humidity of 95%-97% for curing. After the curing is completed, the final high-ductility concrete is obtained.

[0048] Comparative Example 1 This comparative example is compared with Example 1 to examine the influence of coral sand on concrete materials. Compared with Example 1, except that coral sand is not added, the production process of the high ductility concrete of this comparative example is consistent with that of Example 1.

[0049] Comparative Example 2 This comparative example is compared with Example 2 to examine the influence of quartz powder and silica fume on concrete materials. Compared with Example 2, except that quartz powder and silica fume are not added, the production process of the high ductility concrete of this comparative example is consistent with that of Example 2.

[0050] Comparative Example 3 This comparative example is compared with Example 3 to examine the influence of the water glass solution on the concrete material. Compared with Example 3, except that the water glass solution is not added, the production process of the high ductility concrete of this comparative example is consistent with that of Example 3.

[0051] Comparative Example 4 This comparative example is compared with Example 4 to examine the influence of basalt fiber and glass fiber on concrete materials. Compared with Example 4, except that basalt fiber and glass fiber are not added, the production process of high ductility concrete in this comparative example is consistent with that in Example 4.

[0052] The comparison of high ductility performance of concrete in Examples 1-4 and Comparative Examples 1-4 is shown in Table 1.

[0053] Compressive strength (28d) / MPa Bending strength (28d) / MPa Example 1 64.5 12.8 Example 2 63.8 13.2 Example 3 67.3 12.3 Example 4 61.7 14.8 Comparative Example 1 55.2 7.6 Comparative Example 2 54.4 7.2 Comparative Example 3 56.9 8.2 Comparative Example 4 59.2 8.6 .

[0054] in conclusion: Comparative Example 1 is compared with Example 1 to examine the effect of coral sand on concrete materials. Compared with Comparative Example 1, the compressive strength of Example 1 is increased by 9.3 MPa, an increase of about 116.8%; the flexural strength is increased by 5.2 MPa, an increase of about 168.4%.

[0055] Comparative Example 2 is compared with Example 2 to examine the effects of quartz powder and silica fume on concrete materials. Compared with Comparative Example 2, the compressive strength of Example 2 is increased by 9.4 MPa, an increase of about 117.3%; the flexural strength is increased by 6.0 MPa, an increase of about 183.3%.

[0056] Comparative Example 3 is compared with Example 3 to investigate the effect of water glass solution on concrete materials. Compared with Comparative Example 3, the compressive strength of Example 3 is increased by 10.4 MPa, an increase of about 118.3%; the flexural strength is increased by 4.1 MPa, an increase of about 150.0%.

[0057] Comparative Example 4 is compared with Example 4 to examine the effects of basalt fiber and glass fiber on concrete materials. Compared with Comparative Example 4, the compressive strength of Example 4 is increased by 2.5 MPa, an increase of about 104.2%; the flexural strength is increased by 6.2 MPa, an increase of about 172.1%.

[0058] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A high ductility concrete material prepared using coral sand, characterized in that: The invention comprises the following components: cement; red mud; coral sand; fly ash; quartz powder; silica fume; water glass solution; basalt fiber; glass fiber; water reducing agent; and balance water.

2. The high ductility concrete material prepared using coral sand according to claim 1, characterized in that: The weight proportions of the components are: 220-260 parts of cement; 30-50 parts of red mud; 330-420 parts of coral sand; 100-150 parts of fly ash; Quartz powder 100-150 parts; Silica fume 18-42 parts; 34-48 parts of water glass solution; Basalt fiber 21-84 parts; Glass fiber 18-36 parts; water reducing agent 12-14 parts; The water to cement ratio is 0.4-0.

5.

3. The high ductility concrete material prepared using coral sand according to claim 2, characterized in that: The weight proportions of the components are: 220 parts of cement; 30 parts of red mud; 330 parts of coral sand; 100 parts of fly ash; 100 parts of quartz powder; 18 parts of silica fume; 34 parts of water glass solution; Basalt fiber 21 parts; 18 parts of glass fiber and 12 parts of water reducing agent; The water to cement ratio is 0.

4.

4. The high ductility concrete material prepared using coral sand according to claim 2, characterized in that: The weight proportions of the components are: 260 parts of cement; 50 parts of red mud; 420 parts of coral sand; 150 parts of fly ash; 150 parts of quartz powder; 42 parts of silica fume; 48 parts of water glass solution; 84 parts of basalt fiber; Glass fiber 36 parts; water reducing agent 14 parts; The water to cement ratio is 0.

5.

5. The high ductility concrete material prepared using coral sand according to claim 2, characterized in that: The weight proportions of the components are: 230 parts of cement; 40 parts of red mud; 360 parts of coral sand; 100 parts of fly ash; 150 parts of quartz powder; 26 parts of silica fume; 40 parts of water glass solution; 40 parts of basalt fiber; Glass fiber 22 parts; water reducing agent 12 parts; The water to cement ratio is 0.

44.

6. The high ductility concrete material prepared using coral sand according to claim 2, characterized in that: The weight proportions of the components are: 250 parts of cement; 45 parts of red mud; 380 parts of coral sand; 150 parts of fly ash; 150 parts of quartz powder; 38 parts of silica fume; 40 parts of water glass solution; 76 parts of basalt fiber; Glass fiber 32 parts; water reducing agent 11 parts; The water-cement ratio is 0.

48.

7. The high ductility concrete material prepared using coral sand according to claim 1, characterized in that: The cement is high-grade P•II52.5 general-purpose silicate cement (grade 52.5 silicate cement, grade 52.5 ordinary silicate cement, grade 52.5 pozzolanic silicate cement, grade 52.5 composite silicate cement), high-grade 52.5 special silicate cement, and high-grade aluminate cement; The red mud is red mud powder, which is obtained by air-drying red mud slurry or drying it at 90-100° C. until the moisture content is less than 3%, and then crushing it; The particle size of the coral sand ranges from 0.075 mm to 2.36 mm, the main particle size is 0.5 mm to 1.5 mm, and the fineness modulus is between 1.8 and 2.25; The fly ash particle size is 5-25µm; the fly ash has a specific surface area of ​​1300m2 / kg, a loss on ignition of 2.8%, a density of 2.55g / cm3, a SiO2 content of 45.1%, a water content of 0.85%, and a fineness of 16%; The quartz powder has a particle size of 10-60 μm, and the main particle size is 20-45 μm. The silica fume particle size is 20-80 μm, and the main particle size is 30-50 μm.

8. The high ductility concrete material prepared using coral sand according to claim 1, characterized in that: The molecular formula of the water glass solution is Na2O· n SiO2; the modulus n=SiO2 / Na2O (molar ratio) in the water glass solution sodium silicate is between 1.5-3.5; The elastic modulus of the basalt fiber is 91GPa-110GPa, the nominal length is 10mm, the density is 2.63g / cm3-2.65g / cm3, the single fiber diameter is 7μm-15μm, and the breaking strength is greater than 2000MPa; The glass fiber has an elastic modulus of 70-80 GPa, a nominal length of 6-12 mm, a density of 2.4-2.7 g / cm3, a breaking strength of 400-600 Mpa, and a melting point of 680°C; The polycarboxylate water-reducing agent has a solid content of 38%-40% and a water reduction rate of 27%-30%. The polycarboxylate water-reducing agent can reduce the amount of water used and effectively increase the fluidity of the slurry, which is beneficial for the cementitious material to penetrate into the pores.

9. A method for preparing a high ductility concrete material using coral sand, characterized in that: The following steps are included: (1) Weigh all raw materials according to the above ingredient requirements and set aside; (2) soaking the coral sand weighed in step (1) in seawater for pre-wetting for 50 minutes, then taking it out and letting it air dry for 10 minutes without dripping water for later use; (3) Mix cement, red mud, coral sand, fly ash, quartz powder and silica fume and stir them evenly for 5-15 minutes to obtain a cementitious material; (4) adding a portion of water and water glass solution; a water reducing agent to the gelling material prepared in step (3), mixing and stirring until uniform, the stirring time is 15-25 minutes, to obtain a gelled slurry; (5) adding the remaining water and basalt fiber and glass fiber to the gelled slurry prepared in step (4) and mixing and stirring until uniform. The stirring time is 15-25 minutes to obtain a high ductility concrete material. (6) pouring the obtained high ductility concrete material into a mold, placing the test mold on a vibration table in advance, and turning on the vibration table to vibrate after pouring; (7) After the vibration is completed, the module is left to stand for 24 hours for demoulding, and the module is placed in a curing box at a temperature of 25°C-28°C and a humidity of 95%-97% for curing. After the curing is completed, the final high-ductility concrete is obtained.